Guns, Gun Violence and Gun Homicides Perspectives from the Caribbean, Global South and Beyond - Wallace, Wendell C. (Palgrave Studies in Risk, Crime and Society, 2022)
XXXII, 360 p. 27 illus., 15 illus. in color.